Pengaruh Pertumbuhan Ekonomi, Upah Minimum Dan Tingkat Pendidikan Terhadap Penyerapan Tenaga Kerja Di Kota Salatiga - Tri Maryani; Samtono Samtono (Pusat Riset dan Inovasi Nasional, 2023)
Quantitative research is a research method based on the philosophy of positivism, used for research with a certain population or sample, data collection uses research instruments, data analysis is statistical, with the aim of testing the hypotheses that have been set. The population is the area of ​​generalization which consists of: objects/subjects that have qualities and characteristics that are applied by researchers to be studied and conclusions drawn. The population in this study are reports and publications of Economic Growth/PDRB data, Minimum Wage, Education Level and Labor Absorption in Regencies/Cities published by the Central Bureau of Statistics for the City of Salatiga. The method used in sampling in this study was purposive sampling, namely a sampling technique with certain considerations. The determination used purposive sampling because the researcher determined several criteria used, namely available and published data for Regency/City data in the last three years obtained and summarized from the Central Bureau of Statistics for the City of Salatiga. Based on the results of data analysis and discussion obtained from the study entitled